The Wolves at My Shadow: The Story of Ingelore Rothschild - Ingelore Rothschild, edited by Darilyn Stahl Listort and Dennis Listort (Our Lives: Diary, Memoir, and Letters, 2017)
Ingelore Rothschild was twelve years old when she was whisked out of her home in 1936. It was her first step on a cross-continent journey to Japan, where she and her parents sought refuge from rising anti-Semitism in Nazi Germany. A decade later, as she sails away from what has become her home in Kobe, Japan, Ingelore records her memories of life in Berlin, the long train journey through Russia, and her time in Japan during World War II.Each leg of the journey presents its own nightmare: passports are stolen, identities are uncovered, a mudslide tears through the Rothschild's home, and the atomic bombs are dropped on Nagasaki and Hiroshima. Ingelore's bright, observant nature and remarkable capacity for befriending those along her way fills her narrative with unique details about the people she meets and the places she travels to. The story of Ingelore and her prominent German Jewish family's escape is an invaluable account that contributes to Holocaust witness and memoir literature. Although she was forever marked by her traumatic past, Ingelore's survival story is a painful reminder that only European Jews with significant financial means were able to carefully orchestrate an escape from Nazi Germany.